Analisis Kepedulian Pelaku UMKM dalam Menjaga Kebersihan di Lingkungan III Kelurahan Denai (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
This study aims to analyze the level of concern of Micro, Small, and Medium Enterprises (MSMEs) in maintaining environmental cleanliness in environment III, Denai Village. Environmental cleanliness is an important aspect in the sustainability of business activities, but is often ignored by MSMEs due to various limitations. The approach used is a descriptive qualitative approach, with data collection methods in the form of observation, in-depth interviews, and documentation. The results of the study indicate that most MSMEs understand the importance of environmental cleanliness, but its implementation in the field is still limited. Some of the obstacles faced include the lack of supporting facilities, minimal socialization from the local government, and low collective awareness among business actors and the surrounding community. This study recommends the need for active involvement of the village government and the formation of an environmental care community among MSMEs to create a clean, healthy, and sustainable business environment.